2021
DOI: 10.1108/jadee-03-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Does farmers' trust towards buyers drive their entrepreneurial orientation?

Abstract: PurposeIn contexts of transition economies generally characterized by weak formal institutions, a rich literature remarks the important role of informal institutions in fostering entrepreneurial ecosystems. Nevertheless, in the agricultural context, little is known yet about how and why institutions shape farmer entrepreneurship. To better understand how informal institutions shape farmer entrepreneurship, this paper investigates how farmers' trust towards their buyers influence their entrepreneurial orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
2
6
0
Order By: Relevance
“…Second, we show that the farmer-buyer relationship may be viewed as an antecedent of farmer EO. This corroborates with the findings of Xhoxhi et al (2021) who found that farmer EO is shaped by the relationship that they build and maintain with their buyers. Furthermore, our finding strengthens the argument by Rwehumbiza and Marinov (2019) that informal institutions in Kenya and Tanzania shape entrepreneurial orientation.…”
Section: Theoretical and Managerial Implicationssupporting
confidence: 90%
“…Second, we show that the farmer-buyer relationship may be viewed as an antecedent of farmer EO. This corroborates with the findings of Xhoxhi et al (2021) who found that farmer EO is shaped by the relationship that they build and maintain with their buyers. Furthermore, our finding strengthens the argument by Rwehumbiza and Marinov (2019) that informal institutions in Kenya and Tanzania shape entrepreneurial orientation.…”
Section: Theoretical and Managerial Implicationssupporting
confidence: 90%
“…(2014), we conduct exploratory factor analysis (EFA) to check the factor structure and confirmatory factor analysis (CFA) to assess psychometric properties, i.e. reliability, validity and measurement model fit (Xhoxhi et al. , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…POQ refers to the power intermediaries have to ensure product quality and compliance with food safety standards, which benefits both farmers and intermediaries. POM, on the other hand, refers to the power intermediaries use to exploit farmers, leading to reduced trust, reduced investments, and short-term thinking (Xhoxhi et al, 2018(Xhoxhi et al, , 2020(Xhoxhi et al, , 2022a. Xhoxhi et al (2018Xhoxhi et al ( , 2020 have shown that reorienting power from POM to POQ can improve farmer-intermediary relationships and promote high-value crops, reduce conflict, and encourage organic production, thereby making agrifood value chains more sustainable in economic, social, and environmental respects (cf.…”
Section: The Power Narrativementioning
confidence: 99%